Thursday

April 24, 2014

April 24, 2014

Posted by **mary** on Thursday, June 6, 2013 at 2:21pm.

- elementary algebra -
**Kuai**, Thursday, June 6, 2013 at 2:38pm(3b+1) (3b +1) = 16

9b^2 + 3b +3b + 1 = 16

9b^2 + 6b + 1 = 16

9b^2 + 6b + 1 -16 = 16-16

9b^2 + 6b -15 = 0

3(3b^2 + 2b -5) = 0

3(b-1)(3b+5) = 0

b - 1 = 0 3b + 5 = 0

b -1+1 = 0 + 1 3b + 5 - 5 = 0-5

b = 1 3b = -5

3b/3 = -5/3

b = -5/3

b = 1, -5/3

- elementary algebra -
**Steve**, Thursday, June 6, 2013 at 3:15pm(3b+1)^2=16

3b+1 = ±4

3b+1 = 4

b = 1

or

3b+1 = -4

b = 5/3

**Related Questions**

algebra 1 - a+(3a-2a)-(4a-3b) Combine the "a" tems and you can reduce this to _?...

algebra - a^6b^8-a^4b^3+a^3b^5-a^3b^3 ???

Elementary Algebra - Can you help me solve this problem by elimination? 4x-2y=16...

intermediate algebra - combine like terms. write all answers in order 9b^5+3b^2-...

math - algebra - When solving equations by adding integers, what does it mean ...

ALGEBRA 1 - Reiny Thanks for your help. But you lost me. I still end up with...

math - correct or not? 1. 2k = 5/6 k= 5/12? 2.3b= 4/7 b= 4/21? 3. 2/3 d = 5/8 d...

Algebra - Can you solve this problem? 2a+b/(a-b)(a-2b) - a+4b/(a-b)(a-3b) - a-7b...

exponents - simplify the following. leave answers with positive exponents 1) c^2...

algebra - this tells me to rewrite the expression using the distributive ...